Thermal analysis study of some transition metal complexes by TG and DSC methods - Sekerci, M; Yakuphanoğlu, Fahrettin (Springer, 2004)
The thermodynamic and thermal properties of [Cu(L)(2).Cl-2], [Ni(L)(2)].Cl-2, [Co(L)(2).Cl-2]; L= 1,2-bis( o-aminophenoxy) ethane (BAFE), complexes have been investigated. The thermal decomposition of the complexes took place in two distinct steps in endothermic reaction up to 700 degreesC. The activation energy E, the entropy change DeltaS(#), enthalpy DeltaH change and Gibbs free energy change DeltaG(#) were calculated from the results of thermogravimetry analysis (TG) and heat capacity from the results of differential scanning calorimetry (DSC). It was found that the thermal stabilities and activation energies of the complexes follow the order Ni(II)> Cu(II)> Co(II) and E-Co< E-Ni< E-Cu, respectively.
Keywords: thermal analysis; thermodynamic parameters; transition metal complexes